The quality of student critical thinking: A survey of high schools in Bengkulu, Indonesia - Apriza Fitriani; Siti Zubaidah; Nurkhairo Hidayati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Critical thinking skills are among the main skills in the 21st Century. However, many schools in Indonesia have not trained their students' critical thinking skills optimally. The purpose of this study was to identify the quality of high-school students' critical thinking skills. A survey was conducted to 175 tenth graders who were registered in the academic year of 2017/2018. The participants came from five different state senior high schools in Bengkulu, Indonesia. An essay test was used as an instrument to measure the students' critical thinking skills. The results showed that the students' average scores on providing simple explanations, presenting advanced delineation, and making assumptions and integration were in low category (48.15, 49.46, 50.25, respectively). On the other hand, the participants obtained medium scores on decision making (68.04) and conclusion drawing (65.24) and a good score on the management of strategies and tactics (70.00). It can be concluded that the overall rating of the students' CTS was weak, and therefore requires appropriate handling. These results indicate that it is necessary to apply learning strategies that can improve students' critical thinking skills in class.